Development of camel milk soft cheese with different levels of salt, fat and solid not fat - Batool, Aasma; Haq, Faizan Ul; Ali, Khubaib; Khalid, Muhammad Umair; Zafar, Usama; AL-Ansi, Waleed (International Journal of Environment, Agriculture and Biotechnology, 2024)
Camel milk is unique from other ruminant’s milk in terms of its composition as well as in its health effects. Cheese production from camel milk is considered to be a difficult task due to unique physicochemical properties and its compositional structure. The basic purpose of this research was to optimize the processing conditions of camel milk cheese by using different levels of solid not fat (SNF), fat and CaCl2. Buffalo milk (0.0%, 05%, 10%, and 15%) was mixed with camel milk and the cheese produced, shown better results (protein 17.86%, fat 16%, moisture 64.66%) as compared to other concentrations. The cheese with skimmed camel milk incorporated with 5% buffalo milk gave highly significant (p<0.01) results with maximum yield 21.15%, fat 15%, acidity 3.10%, moisture 68% and protein 16.71% with good texture as compared to cheese from whole camel milk and skimmed camel milk. While, for the CaCl2 addition (0.0%, 0.3%, 0.6% and 0.9%) the cheese with 0.9% CaCl2 resulted in increased yield (5 %) with an improved texture and coagulation time (p<0.01).